[Thatched cottage] - Hall, S. C., Mrs., 1800-1881 (1840)
Thatched cottage in a rural setting.
Attributed to unidentified artist.
Catalogue of Irish Topographical Prints and Original Drawings / Rosalind M. Elmes ; New edition revised and enlarged by Michael Hewson - Dublin : Malton Press, 1975
Ireland: its scenery, character, &c / Mr. & Mrs. S. C. Hall - London: How and Parsons, 1841-43.
Keywords: Thatched roofs -- Ireland -- 1830-1840; Dwellings -- Ireland -- 1830-1840; Ink drawings -- Irish -- 1830-1840.; Landscape drawings -- Irish -- 1830-1840.; Wash drawings -- Irish -- 1830-1840